Mobile VoIP : managing , scheduling and refining voice packets to and from mobile phones - Salam, Mohammad Abdus; Biswas, Tapan (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2006.